Managing departmental knowledge through an open source E-portal / Gan See Leng - Gan, See Leng (2008)
The purpose of this research is to analyze whether an open source knowledge management e-portal can be used to manage, share, retain and capture the organization or departmental knowledge which could be lost due to retirement, resignation of employees or improper management of knowledge. There is no specific definition of what organization or departmental knowledge is but generally it can be described as the knowledge sourced from the organization or department which are held by its employees or are recorded in some materials such as books, documents, logs and etc. Many organizations do not know what their organization or departmental knowledge is or what they know as their knowledge is poorly organized and often disappears in archives or lost forever. This research which uses empirical research methodology that based its results on observation and experiment was done on 10 employees working in data centre at NTTMSC Sdn Bhd, Cyberjaya. The research shows that open source knowledge management e-portal can also be effectively used to manage, share, retain and capture the organization or departmental knowledge.